Cochlear implant candidates with psychogenic hearing loss. (April 2015) - Kompis, Martin; Senn, Pascal; Mantokoudis, Georgios; Caversaccio, Marco
Abstract: Conclusions: Specific requests for cochlear implantations by persons with psychogenic hearing loss are a relatively new phenomenon. A number of features seems to be over-represented in this group of patients. The existence of these requests stresses the importance of auditory brainstem response (ABR) measurements before cochlear implantation. Objective: To describe the phenomenon of patients with psychogenic hearing losses specifically requesting cochlear implantation, and to gain first insights into the characteristics of this group. Methods: Analysis of all cases seen between 2004 and 2013 at the University Hospital of Bern, Switzerland. Results: Four cochlear implant candidates with psychogenic hearing loss were identified. All were female, aged 23–51 years. Hearing thresholds ranged from 86 dB to 112 dB HL (pure-tone average 500–4000 Hz). ABRs and otoacoustic emissions (OAEs) showed bilaterally normal hearing in two subjects, and hearing thresholds between 30 and 50 dB in the other two subjects. Three subjects suffered from depression and one from a pathologic fear of cancer. Three had a history of five or more previous surgeries. Three were smokers and three reported other close family members with hearing losses. All four were hearing aid users at the time of presentation.